Developing supplementary writing tasks for semester 3 students of English Education Department of STAIN Gajah Putih - Sungkawati Kardi Wahyuningsih (LPPM UNY, 2014)
The research study was aims to develop writing tasks for supplementary material for semester 3 students of English Education Department of STAIN Gajah Putih, Takengon. This research was a research and development study that included the steps of needs analysis, course grid design, product development, product validation, try-out, and study of the final product. This research developed seven units of writing tasks developed according to the needs analysis data. The need of semester 3 students of STAIN Gajah Putih is to improve their writing skills. The needs-related appropriate supplementary writing tasks in terms of their components are: the goal of learning writing is to improve the students’ writing skills; the input presents interesting pictures and texts; the procedure presents interesting and enjoyable activities; the learners’ role is as the active learner; the teacher’s role is the feedback giver; and the setting is individual work. The components of appropriate supplementary writing tasks in terms of their organizations are arranged into seven stages. They are get ready, take action, structure focus, writing focus, writing process, check competence, and make summary